Platform Solutions for Digital Transformation of Production and Logistics Systems - O. V. Miasnikova (Цифровая трансформация, 2020)
The work is devoted to the problem of platform solutions using for the digital transformation of production and logistics systems. The purpose of this article was a development of approaches to the services formation and filling of the digital platforms. The role and place of digital platforms in the transition of industrial enterprises to work on the models of "manufacturing as a service", "sharing using" of a circular economy, integrated execution by an international supply chain links of a geographically distributed business process are determined. The need for solving the problems of cooperation between production and logistics links based on digital platforms has been identified. In contrast to the existing researches, the article addressed the methodological issues of designing the digital platforms functionality to solve the logistic problems of business, cooperation and coordination of participants in digital platforms. In the work, general scientific methods were used to cognize economic phenomena and processes (analysis and synthesis, a systematic approach, the dialectical method, etc.). The main study results were methodological approaches to the formation of a digital platform as an ecosystem; designing its functional component. The author offered methodological approaches to services designing based on continuous engineering and agile design. The using area of the proposed solutions: the design of applied digital platforms and logistics service systems for certain production and logistics systems.